Business Fluctuations in MERCOSUR: Some recent stylized facts - Jacobo, Alejandro Damián (2026)
This work documents the existence of similarities in business fluctuations of the Southern Common Market (MERCOSUR) countries for the last quarter of a century. Argentina presents the highest volatility and the trembles that come into being in its economy are two and a half times more intense than those of Brazil, its main trading partner. Despite the concomitance equal to or greater than 60% on GDP fluctuations, the countries are weakly correlated with the exception of Argentina and Uruguay. The Consumption is 50% more volatile with respect to GDP in the case of Uruguay, and the volatility for the Gross Capital Formation is respectively 200 and more than 300% for Argentina and Uruguay. The Trade Balance exhibits the lowest relative volatility and importantly exerts its countercyclically role in Argentina and Brazil. Although the economies present some interesting parallel variations as long as they simultaneously remain in the same phase of the economic cycle, the volatility of one of the main economies together with the weak correlation of all countries’ business fluctuations suggest that the success in the application of homogeneous macroeconomic policies is still distant.